Control Issues: Examining the Relationship between Low Self-Control and Intimate Partner Violence for both Perpetrators and Victims - Chintakrindi, Sriram; Gupta, Suditi (International Journal of Criminology and Sociology, 2022)
Gottfredson and Hirschi’s (1990) low self-control theory is linked to individual-level non-violent and violent criminal offending. In this study, we examine secondary-data collected from a transnational sample of survey respondents (n = 17404) to test a predictive model of low self-control on outcomes related to intimate partner violence for both perpetrators and victims. We control for several variables related to socio-demographic characteristics, substance use history, and deviance history when we test our model using logistic regression analysis. The results from our analysis indicates that a unidimensional measure of low self-control is a consistent and statistically significant predictor of outcomes related to intimate partner violence, even when control variables are entered into the model. These findings have strong policy implications for identifying risk-factors and interventions associated with intimate partner violence.